2016
DOI: 10.3329/bmrcb.v41i3.29884
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Feeding Practices and Nutritional Status of Infants in Selected Villages at Dhamrai

Abstract: Infants are the most vulnerable group among all the age groups in our society. Breastfeeding decisions and practices are influenced by multiple factors including knowledge, attitude and beliefs. This rural based cross sectional descriptive study carried out among 320 mothers having infant up to 1 year of selected villages at Dhamrai from 7th August to 31th January 2014, to determine the characteristics of feeding practices and nutritional status of infants. Near fifty percent infants belonged to age group 9-12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This finding agreed with the findings of other researchers [24, 25] showing that malnutrition is indeed a teething public health problem among under-fives. The prevalence of underweight, wasting and stunting in this study was higher than the prevalence of underweight (25%), wasting (9.4%) and stunting (19.2%) among under-fives in a study in Bangladesh [26]. The prevalence reported in the present study was low compared to the prevalence of underweight (33.3%), wasting (26.4%) and stunting (24.6%) reported in a previous study [24].…”
Section: Discussionmentioning
confidence: 74%
“…This finding agreed with the findings of other researchers [24, 25] showing that malnutrition is indeed a teething public health problem among under-fives. The prevalence of underweight, wasting and stunting in this study was higher than the prevalence of underweight (25%), wasting (9.4%) and stunting (19.2%) among under-fives in a study in Bangladesh [26]. The prevalence reported in the present study was low compared to the prevalence of underweight (33.3%), wasting (26.4%) and stunting (24.6%) reported in a previous study [24].…”
Section: Discussionmentioning
confidence: 74%
“…were found in Indian studies, [14][15][16] but it was higher in another study done in Bangladesh. 17 It may be due to better presence of awareness among the mothers residing into that specific region.…”
Section: Resultsmentioning
confidence: 99%
“…20 However, almost similar results were found in other studies done in the country. 1,17,21 Difficulties faced by the mothers for EBF were insufficient secretion of breast milk, absence of knowledge and mother's illness.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the use of pre-lacteal feeds rather than colostrums has been reported to higher at community level in Bangladesh especially in infants born at home1 On the contrary, another study in Bangladesh revealed regarding feeding status most 284(88.8%) of respondents got colostrums. 14 However, trend of giving colostrums reached a tremendous condition that is 96.5% (330/342) a study done in Dhaka slum in Bangladesh. 15…”
Section: Discussionmentioning
confidence: 97%